Libro Libre Beginning Spanish - Huebener, Erin (Open textbook library., 2018)
One of the most important things we can do to hold ourselves accountable for our learning is to engage in goal setting and metacognition—a fancy term for thinking about the way we think and learn. The goals we set should be specific and achievable. Something like “Speak Spanish” is too broad, we need to focus on the steps we need to take to get there and the signs that we will see as proof of our progress.